The Politics of Military Occupation - Stirk, Peter M. R (Edinburgh University Press, 2009)
Stirk argues that military occupation should be regarded as a political phenomenon - a distinct form of government at the heart of which is the nature of obligation on the part of both the occupier and the occupied. He aims to promote a change in the understanding of occupation, thereby avoiding the perpetuation of recent failures in this area.